Developing and Implementing a Software Program for Configuring Three Dairy Corral Designs - Samer, M. (Journal of Experimental Sciences, 2010)
Eleven simulation models were developed to plan and design several dairy farm facilities. A decision tree was developed for each simulation model, and then the simulation models were integrated into the relevant decision trees. C# programming language was used to develop a software program via the simulation models and decision trees. The objective is to develop a software program to plan and design dairy farm facilities for dairy farms in hot climates. ——————————————————————————————————– <div style="border-right: medium none; padding-right: 0in; border-top: medium none; padding-left: 0in; padding-bottom: 1pt; border-left: medium none; padding-top: 0in; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Assistant Professor, Agricultural Engineering Department, Faculty of Agriculture, Cairo University, Gammaa Street, 12613 Giza, Egypt * Corresponding Author, Email: samer@cu.edu.eg Please Cite This Article As:<span style="font-size: 6.5pt; line-height: 150%; font-family: Symbol; mso-ascii-font-family: Tahoma; mso-hansi-font-family: Tahoma; mso-bidi-font-family: Tahoma; mso-char-type: symbol; mso-symbol-font-family: Symbol;"> Â M. Samer. 2010. Developing and Implementing a Software Program for Configuring Three Dairy Corral Designs. J. Exp. Sci. 1(3): 19-22. Â